PSYCHOLOGICAL FACTORS IN SHAPING INVESTOR EXPECTATION ON CAPITAL MARKETS - Mikołajek-Gocejna, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Investor expectations about the course of future economic processes are one of the key factors influencing their decisions. It seems that expectations play a particular role because they constitute unobservable variables that can account for observable economic phenomena. Getting to know the process of how investor expectations are formed is a crucial element of description, interpretation and forecasting changes in the value of assets on financial markets, and especially changes in stock prices on capital markets which affect the value of publicly traded companies. The aim of this paper is to present the psychological factors shaping investor expectations and influencing the market value of companies, factors determining both the motivational and cognitive inclinations of investors. The main questions that arise from the background of the analysis conducted in this paper are: 1. whether awareness of the psychological determinants of investment decisions enables companies to consciously create long-term investor expectations, inspiring, in a sense, a more fundamental response from the capital market, 2. whether there is the potential to include investor expectations in the value-‑based management process and to make the transition from value-based management to expectations-based management.